2019
DOI: 10.20524/aog.2019.0367
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on the incidence and severity of post-endoscopic retrograde cholangiopancreatography pancreatitis

Abstract: Background Pancreatitis is a potential major complication after endoscopic retrograde cholangiopancreatography (post-ERCP pancreatitis; PEP). Obesity has been associated with increased severity of acute pancreatitis. However, the correlation between obesity and PEP is controversial. Therefore, our study aimed to clarify the relationship between body mass index (BMI) and the incidence and severity of PEP. Methods A retrospective cohort study was conducted to elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
3
3
1
Order By: Relevance
“…Our finding of no significant association between the gender of the patients and development of PEP corresponds with the results from another similar studies [17,23,24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of no significant association between the gender of the patients and development of PEP corresponds with the results from another similar studies [17,23,24].…”
Section: Discussionsupporting
confidence: 92%
“…The PEP incidence of 16,7% in our study patients group was higher in comparison to 3-10% reported in the systematic review paper [23].…”
Section: Discussioncontrasting
confidence: 73%
“…A retrospective study, including 583 patients, revealed a significantly higher PEP rate in obesity and a lower rate in normal weight 11 . However, another study, including 2235 patients, indicated that neither obesity nor low body weight increased PEP's incidence or severity 12 …”
Section: Introductionmentioning
confidence: 98%
“…11 However, another study, including 2235 patients, indicated that neither obesity nor low body weight increased PEP's incidence or severity. 12 This study aimed to investigate the effect of obesity and morbid obesity in patients undergoing ERCP by performing a three-way PSmatching analysis on both the full cohort and again on a restricted cohort that excluded smokers, alcoholics, and patients with chronic illness to avoid reverse causation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an exhaustive review of current academic literature, an explanation for why an increased BMI may impart a greater likelihood of ERCP has not been well established in current academic literature. However, obesity has been established as an independent risk factor for developing post-ERCP pancreatitis, potentially due to a low-grade chronic inflammatory state related to a decreased level of adiponectin, an anti-inflammatory adipokine [14]. Nonetheless, it is reasonable to conclude that patient selection influences the utility of AUS following negative CTAP and may have a greater effect on management in patients with elevated BMI or advanced age.…”
Section: Discussionmentioning
confidence: 99%